2014
DOI: 10.1111/ppl.12170
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal water dynamics in mature Banksia menziesii trees during drought

Abstract: Southwest Australian Banksia woodlands are highly diverse plant communities that are threatened by drought- or temperature-induced mortality due to the region's changing climate. We examined water relations in dominant Banksia menziesii R. Br. trees using magnetic leaf patch clamp pressure (ZIM-) probes that allow continuous, real-time monitoring of leaf water status. Multiple ZIM-probes across the crown were complemented by traditional ecophysiological measurements. During summer, early stomatal downregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
(67 reference statements)
0
13
0
Order By: Relevance
“…Brouwers et al 2012). Here, forest tree species are increasingly showing severe dieback and mortality in response to extreme climatic conditions (Matusick, Ruthrof & Hardy 2012;Matusick et al 2013;Bader et al 2014), but whether this constitutes a tipping point is unclear. Allen et al (2010) concluded that in already dry regions, forests are most vulnerable to further drought possibly indicating reduced resilience.…”
Section: O C a L S C A L E R E S P O N S E Smentioning
confidence: 99%
“…Brouwers et al 2012). Here, forest tree species are increasingly showing severe dieback and mortality in response to extreme climatic conditions (Matusick, Ruthrof & Hardy 2012;Matusick et al 2013;Bader et al 2014), but whether this constitutes a tipping point is unclear. Allen et al (2010) concluded that in already dry regions, forests are most vulnerable to further drought possibly indicating reduced resilience.…”
Section: O C a L S C A L E R E S P O N S E Smentioning
confidence: 99%
“…Chronic water stress commonly increases background mortality rates in tree populations (Pangle et al 2015, Berdanier andClark 2016), and incites tree decline (Bigler et al 2006), especially when opportunistic pests and pathogens are present (Hart et al 2014). In contrast, short-term drying and heating events, such as acute drought and heat waves, cause severe acute water stress in trees, typified by rapid loss of stem conductivity and leaf turgor (Anderegg et al 2014, Bader et al 2014, leading to tree crown dieback, tree mortality, and widespread forest mortality in severe cases (Anderegg et al 2015). Of particular interest, however, are the interacting and compounded effects of chronic and acute drought and heat events on trees and forests, since both climatic averages and extreme events are predicted to change for many areas of the world over the coming decades (Collins et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…acute warming) on trees is at its infancy. Heat waves have been shown to negatively affect the growth of trees (Pichler and Oberhuber 2007), and have sometimes occurred concurrently with observations tracking tree mortality (Matusick et al 2012, Bader et al 2014, Mitchell et al 2014. The resilience of trees to the primary and secondary effects of heat waves is not well understood, especially when combined with drought (Teskey et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The dry winters of 2009 and 2010, coupled with elevated summer temperatures in 2009, 2010 and 2011 between 4-6 • C above the average monthly temperatures ( Figure 2C) are associated with the greatest occurrence of tree mortality in the park ( Table 7). Other studies conducted within the southwest of Western Australia (SWWA) [1,8,51,77,78] have also linked tree mortality in 2011 to this period of sustained drought and heat. Following the combined drought/heat event of 2009/2010/2011, the above average winter rainfall in 2011 and 2013 ( Figure 2A), coupled with summer storms in late-2011 and early-2013 ( Figure 2B), likely recharged the vadose zone and water table, with the recovery of trees in 2014 indicative of this process.…”
Section: Patterns and Drivers Of Tree Declinementioning
confidence: 99%